Pengukuran Kinerja Non Finansial: Suatu Cara meningkatkan ‘Value’ Perusahaan - Ietje Nazaruddin (Journal of Accounting and Investment, 2000)
The primary purpose performance evaluation is to motivate employees to attain organizational goals and to comply with predetermined behavior standards to produce desire actions and out comes. The behavior standards could be prescribed managerial policies or formal plans for desire integrated actions (Siegel, 1989). Innovation in measuring the financial performance of these organizations played a vital role in their successful growth at the industrial age. Unfortunately, Financial measure are used for monitoring purpose are not under the complete control of the people being monitored (Zimmermen, 1995). At its heart, an overemphasis on achieving and maintaining short-term financial results can cause companies to overinvest in short-term fixes and to underinvest in long-term value creation, particularly in the intangible and intellectual assets that generate (Kaplan, 1999) The emergence of the information era requires the new measurements systems, that complete financial measurement to improve competitive organizations. The non-financial measurement complement financial measures of the drivers of future performance to superior performance. Non financial measure can solve to overemphasis maximize short-term financial result if only financial measure uses. Kaplan introduces the way to solve the irresistible force to build long-range competitive capabilities and the immovable object of the historical-cost financial accounting model has created a new synthesis: the Balanced Scorecard